Presentation of Restrictive and Repetitive Behaviors in Autism Spectrum Disorder - Muhammad Basit, Allah Nawaz Sultan, Shabir Ahmed, Nosheen Iftikhar, Waheed Ahmad,,Muhammad Hafeez, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Autism spectrum disorders (ASDs) are lifelong developmental disabilities characterized by marked difficulties in social reciprocal interaction and communication, along with restricted and repetitive interests, attitudes and behaviors. Aim: To determine the frequency and spectrum of restrictive and repetitive interests, attitudes and behaviors in patients with ASD. Methods: A Descriptive cross sectional study was carried out at The Children’s Hospital & Institute of Child Health, Lahore for six months. A total of 190 cases were enrolled in this study, Patients assessed for presence of restrictive and repetitive interests, attitudes and behaviors and its types including; Stereotyped or repetitive motor movements, insistence on sameness, highly restricted, fixated interests and Hyper or Hypo reactivity to sensory input. All the data was entered and analyzed on SPSS. Results: The mean age of patients was 6.54±2.29 years. Male to female ratio was 1.63:1. The mean CARS score was 42.12±7.31. The restricted and repetitive interests, attitudes and behaviors were noted in 180(94.7%) patients. Conclusion: Repetitive behavior was noted in 94.7% patients, stereotypies, insistence on sameness, highly restricted interests and hyper of hypo reactivity to sensory input was found in 42.6%, 30.5%, 10.5% and 11.05% respectively